Real-time monitoring of food freshness using delphinidin-based visual indicator - Husin, Nurdiyana; Abdul Rahim, Mohd. Zulkhairi; Mohd. Noor, Mohd. Azizan; Mohammad Rashedi, Ismail Fitry; Hassan, Nazatulshima (Malaysian Analytical Sciences Society, 2020)
Nowadays, there is an increasing demand from consumers for better quality and hygienic food products, particularly for vulnerable foods that are easily infected by microorganisms. At present, consumers only depend on the expiry date, but this information does not always portray the real indication of the actual progress of food spoilage. The use of a colorimetric freshness indicator can provide direct and real-time visual quality information, but most of the previous works focused on synthetic colours. In this project, a natural colour (anthocyanin-delphinidin derivative) from Clitoria ternatea (butterfly pea) flower was extracted using an ultrasonic processor, followed by immobilisation on indicator strips, and finally applied as a freshness indicator for the qualitative detection of beef freshness. The extracted colour changed obviously at different pH values, from dark blue (pH 5.93) to green (pH 8) and yellow at pH 12. The delphinidin-based visual indicator was also able to detect the spoilage of beef at hour 18 (pH 6.76 ± 0.29 and point of rejection at 25.67 ΔE*) at room temperature (25 ± 1 °C) and on day 6 (pH 6.71 ± 0.05 and point of rejection at 27.09 ΔE*) in chiller storage (4 ± 1 °C). The tested visual indicators at room and chiller temperature responded to the changes of pH as volatile compounds were gradually produced from the spoiled product. The colour of the indicators subsequently changed from dark blue to green and was easily visible to the naked eye. This study provides a foundation for developing a new visual indicator for monitoring real-time beef freshness and may also be used for intelligent packaging.